The Relationship between Communication in the Family and Early Childhood Self-Confidence in PAUD Mutiara Bunda Padang City - Gita Atika, Raras; Ismaniar, Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
ABSTRACTThis research was motivated by the low self-confidence of young children in PAUD Mutiara Bunda Padang City. This research aims to describe communication within the family, the self-confidence of young children, and the relationship between communication within the family and the self-confidence of young children at PAUD Mutiara Bunda Padang City. The approach in this research was carried out quantitatively with a correlational type. The population at the research location was 28 subjects (children), represented by 28 subjects' parents. The sample was 75% of the total population, namely, 21 children represented by 21 parents, with a sampling technique called simple random sampling. The data collection instrument uses a questionnaire. The analysis technique uses a percentage formula, and to find correlations, the Spearman rho formula is used. The results of this study show that: (1) Parental communication in the family with children is categorized as poor. (2) Early childhood self-confidence is categorized as low; (3) There is a significant relationship between communication within the family and the self-confidence of young children at PAUD Mutiara Bunda Padang City. Keywords: Parent Communication, Self-Confidence, Early Childhood